Becoming Beside Ourselves : The Alphabet, Ghosts, and Distributed Human Being - Rotman, B. (Brian) (Book collections on Project MUSE., 2008)
Theoretical study of the relationship between technoscience and the human body that examines the ways in which bodies and machines "speak" not just through language but also through gesture, numbers, and other non-alphabetic systems of expressio